Trends in Worldwide Research in Hypertension Over the Period 1999–2018: A Bibliometric Study. Issue 5 (November 2020) - Devos, Patrick; Ménard, Joël
Abstract : Bibliometric analysis, a powerful tool for assessing trends in research output, was employed to analyze the evolution of hypertension research over a 20-year period. The analysis was based on 90 308 original articles and a citation analysis. The use of bibliometric as a potential tool for shaping research policy at the institution or country level was also explored. The number of published hypertension articles increased by 43.5% over the 20-year period. By contrast, the increase in the number of articles in all medical disciplines was 96%, and in the cardiovascular field was 64%. Of the 6 countries producing the largest number of articles, the United States was consistently the major contributor. There was a slight decrease from Japan, a slight increase from the United Kingdom, and relatively stable output from Germany and Italy over the study period. Output from China showed the strongest growth. The trends in Specialization Index and Category Normalized Citation Impact varied by country. In Russia, Poland, and Brazil, increases in output were greater for hypertension research than for medical research in general. The United Kingdom and Denmark had greater hypertension research output than the other countries. VOSviewer analysis showed an intensification of collaborations between countries and a shift, over 10 years, from 3 clusters towards 2 clusters. Such analysis may help to shape research policy at the country level and can be similarly performed for institutions. Historical changes in hypertension research can be monitored over decades if the same channels continue to be used for communication of scientific results. Graphic Abstract—: A graphic abstract is available for this article. Abstract : Supplemental Digital Content is available in the text.